2012
DOI: 10.3109/09637486.2012.749839
|View full text |Cite
|
Sign up to set email alerts
|

Effect of resistant starch on the cooking quality of yam (Dioscoreaspp.) and cassava (Manihot esculenta) based paste products

Abstract: Total starch (TS) and resistant starch (RS) contents in pasty edible product of mealy and hard cooking tubers of three yam varieties and four cassava varieties were determined to evaluate their contribution in their cooking quality. TS and RS contents appeared as the main components in determining yam cooking quality. Mealy cooking yam varieties were characterized by a significant higher TS content (75.2 ± 7.7 g/100 g d.m.) and lower RS content (13.8 ± 3.4 g/100 g d.m.) than hard cooking yam varieties, which, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…For example, RDS, SDS, and RS from 3 genotypes of D. nipponica ranged from 3.4% to 10.2%, 23.5% to 29.3%, and 66.3% to 67.3%, respectively (Jiang and others ). Higher amylose content was associated with higher RS content of starch (Kouadio and others ). The mealy (as opposed to hard) texture of cooked tubers was correlated to a higher total starch and a lower RS content of starch (Kouadio and others ).…”
Section: Enzyme Susceptibility and Nutritional Propertiesmentioning
confidence: 88%
See 1 more Smart Citation
“…For example, RDS, SDS, and RS from 3 genotypes of D. nipponica ranged from 3.4% to 10.2%, 23.5% to 29.3%, and 66.3% to 67.3%, respectively (Jiang and others ). Higher amylose content was associated with higher RS content of starch (Kouadio and others ). The mealy (as opposed to hard) texture of cooked tubers was correlated to a higher total starch and a lower RS content of starch (Kouadio and others ).…”
Section: Enzyme Susceptibility and Nutritional Propertiesmentioning
confidence: 88%
“…Higher amylose content was associated with higher RS content of starch (Kouadio and others ). The mealy (as opposed to hard) texture of cooked tubers was correlated to a higher total starch and a lower RS content of starch (Kouadio and others ).…”
Section: Enzyme Susceptibility and Nutritional Propertiesmentioning
confidence: 88%
“…The candidate gene association analysis enabled the identification of fourteen pectin and three starch candidate genes associated with texture, confirming the involvement of the cell wall and starch content in boiled yam texture (Kouadio et al, 2013). Among the seventeen candidate genes, three have high effect and are involved directly in the cell wall composition.…”
Section: Discussionmentioning
confidence: 62%
“…Such as for cereals and other tuber crops, the total starch content of yams is a primary determinant of tuber quality. Preferred mealy cooking yam cultivars had significantly higher starch content (Kouadio et al, 2013). Among the three genes associated with starch content, the 1,3-beta-glucan synthase had the highest effect.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15] Starch granule size differences have been observed to impact the functional properties of sweet potato and banana. 16,17 According to Kouadio et al, 18 mealy-cooking yam varieties typically have small starch granules (10-30 μm in diameter), while hard-cooking yam varieties have larger starch granules (35)(36)(37)(38)(39)(40) μm in diameter). Additionally, Kang et al 19 demonstrated that the shape of starch granules significantly affected the properties of rice flour and the quality of gluten-free bread made from it.…”
Section: Introductionmentioning
confidence: 99%